The Impact of Acquisition Mode on Expected Speed of Product Mastery and Subsequent Consumer Behavior - Dustin Harding, R; Hildebrand, Diogo; Kramer, Thomas; Lasaleta, Jannine D (Journal of Consumer Research, 2019)
Consumers can obtain skill-based products through a variety of acquisition modes, such as purchase or rental. Despite the rise of nonpurchase acquisition modes, surprisingly little research has explored the effects of differential acquisition modes on consumer behavior. This research begins to fill this gap in the literature by examining the effect of acquisition mode on the expected time necessary to master newly adopted skill-based products and the downstream consequences for consumers and marketers. Results of four experiments and a field study show that purchasing, versus renting, products requiring skill-based learning increases the amount of time consumers expect to be required to master them. Further, the differences in speed of product mastery, in turn, impact subsequent consumer behavior via differential levels of product use commitment.